Macroscopic Changes Observed after Burning in Incised Wounds on Bones Caused by Sharp and Penetrating Instruments: A Preliminary Experimental Study on Bovine Bones - Akrep, Aytunç; Ersoy, Gökhan (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Stab and incised wounds are frequently encountered in forensic practice. Burned skeletal remains often complicate the evaluation of such injuries, making it essential to understand how fire alters cut marks on bones. This study aimed to investigate macroscopic changes in bones subjected to sharp-force trauma after exposure to high temperatures. Methods: Three bovine humeri were incised with a 32 cm non-serrated kitchen knife. The length, width, direction, and interrelationships of each incision were measured with a forensic scale, photographed, and recorded. The bones were then burned in open-air conditions using oak wood, without accelerants, at 460–570 °C for 60 minutes. Following combustion, the incisions were remeasured, and pre- and post-burning characteristics were compared statistically. Results: Despite advanced thermal destruction, most incisions remained macroscopically visible. Heat exposure caused significant increases in incision length and width (p < 0.05). Linear fissures radiating from the cuts were observed, and the cut margins appeared sharper and drier after burning. In one specimen, thermal fractures disrupted the evaluation of a distal incision. Conclusion: Sharp-force trauma marks on bones are not completely obscured by fire and may even become more pronounced. However, heat-related expansion of cut dimensions can lead to overestimation of blade size. These findings emphasize the need for caution in interpreting burned skeletal remains and highlight the importance of further research with larger sample sizes to improve forensic accuracy.